The black widow eaudiobook - Silva, Daniel (Gabriel Allon, 2016)
#1 NYT Bestseller #1 USA Bestseller #1 WSJ Bestseller An Amazon Editors' Best Book of the Year A Kirkus Best Fiction Book of the Year An iBooks Book of the Month "Fascinating, suspenseful, and bated-breath exciting.... Silva proves once again that he can rework familiar genre material and bring it to new life." — Publishers Weekly , starred review "Silva builds suspense like a symphony conductor.... A winner on all fronts." — Booklist , starred review Bestselling author Daniel Silva delivers another spellbinding international thriller—one that finds the legendary Gabriel Allon grappling with an ISIS mastermind. Gabriel Allon, the art restorer, spy, and assassin described as the most compelling fictional creation ""since Ian Fleming put down his martini and invented James Bond"" (Rocky Mountain News), is poised to become the chief of Israel's secret intelligence service. But on the eve of his promotion, events conspire to lure him into the field for one final operation. ISIS has detonated a massive bomb in the Marais district of Paris, and a desperate French government wants Gabriel to eliminate the man responsible before he can strike again. Acclaimed novelist Daniel Silva has thrilled, entertained and educated readers with eighteen thoughtful and gripping spy novels featuring a diverse cast of compelling characters and ingenious plots that have taken them around the globe and back—from the United States to Europe, Russia to the Middle East. From its shocking opening to its explosive denouement in Washington, D.C., The Black Widow reveals itself as Silva's most timely and powerful novel yet. Following the success of his smash hit The English Spy, this electrifying thriller showcases Silva's consummate skill and brilliant imagination, and is sure to be a must read for his multitude of current and future fans.